Pengelolaan Kedisiplinan Berbasis Pendidikan Islam(Studi Kasus Di Sma Muhammadiyah Susukan) - Sunaryo, Sunaryo; , Dr. Sofyan Anif, M.Si; , Dr. Sabar Narimo, M.M., M.Pd (2016)
The purpose ot the research is (1) determine the characteristics of the student discipline-based Islamic education in SMA Muhammadiyah Susukan (2) describes how the management of student discipline-based Islamic education in SMA Muhammadiyah Susukan and (3) determine Applying discipline students based Islamic education in SMA Muhammadiyah Susukan. Research methods, type of research is qualitative, because in studying the problem, the researchers did not prove or disprove the hypothesis made before the study but process data and mengalisis a problem in a non-numeric. Based on a series of theories about the qualitative research, because this kind of research focusing on the description of the data in the form sentences that have profound significance that comes from informants and the observed behavior. The study was conducted from March to May 2016 in the school year 2015-2016. Data collection techniques in research-based Islamic student discipline using (1) the interview method (2) direct observation in the field and (3) use the documentation in the form of school data. The results of the research conducted there are three, namely (1) the characteristics of the discipline of students based on Islam that binds students with rules and regulations nuanced Islamic thus realizing students noble character and berahklakul karimah by habituation and civilize 4S, Smile Speak Greetings and salutations (2) the management discipline students based Islamic education set forth in the rules and regulations of the students started to go to school until the completion of school hours, and (3) the application of the discipline students based Islamic education implemented in the school environment both outside the classroom as well as in the classroom and beyond schools so as to create an atmosphere of faith and continuous.